2021
DOI: 10.22342/jme.12.1.13125.147-158
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Students’ Algebraic Proficiency From a Structure Sense Perspective

Abstract: Structure sense can be interpreted as an intuitive ability towards symbolic expressions, including skills to perceive, to interpret, and to manipulate symbols in different roles. This ability shows student algebraic proficiency in dealing with various symbolic expressions and is considered important to be mastered by secondary school students for advanced study or professional work. This study, therefore, aims to investigate students’ algebraic proficiency in terms of structure sense. To reach this aim, we set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Regarding student difficulties in solving inequalities of task one and two, which related to the use of the procedural strategy, errors in expanding and factorizing algebraic expressions were observed. From the perspective of symbol sense, these difficulties involve an inability in manipulating symbolic expressions in the process of problem solving (Arcavi, 2005;Bokhove and Drijvers, 2010;Jupri and Sispiyati, 2020;Jupri et al, 2021). The difficulties encountered by the students, related to the use of the symbol sense strategy, include errors of canceling out the same factors on both sides of an inequality and therefore, concluding an incorrect solution to the inequality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding student difficulties in solving inequalities of task one and two, which related to the use of the procedural strategy, errors in expanding and factorizing algebraic expressions were observed. From the perspective of symbol sense, these difficulties involve an inability in manipulating symbolic expressions in the process of problem solving (Arcavi, 2005;Bokhove and Drijvers, 2010;Jupri and Sispiyati, 2020;Jupri et al, 2021). The difficulties encountered by the students, related to the use of the symbol sense strategy, include errors of canceling out the same factors on both sides of an inequality and therefore, concluding an incorrect solution to the inequality.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, algebra is considered a subject that is difficult for most students to learn and for teachers to teach (Bokhove and Drijvers, 2012;Chapman, 2006;Carraher et al, 2006;Van Amerom, 2003), and this is also true in Indonesia (Jupri et al, 2014a;Jupri et al, 2015;. Previous studies investigating student difficulties in understanding early algebra, revealed that Indonesian students lack both algebraic procedural skills and conceptual understanding in dealing with equations, algebraic expressions, and word problems (Jupri et al, 2014a;Jupri et al, 2014b;Jupri et al, 2021). There are several factors that contribute to this, one of which is a lack of either the students or teachers' ability to understand algebra.…”
Section: Introductionmentioning
confidence: 99%
“…Problem-solving accuracy and efficiency are primary goals in mathematics education (Common Core State Standards, 2010); however, many students struggle to acquire structure sense—the ability to detect patterns within mathematical notation (e.g., opposites: 3 + (–3); inverses: 4 × 1/4; like terms: 2( x + y ) and 3( x + y ); groups of terms: a x 2 and b x in a x 2 + b x ), derive meaningful interpretations from the notation, and efficiently act on it (Hoch & Dreyfus, 2004; Jupri et al, 2021; Livneh & Linchevski, 2007). In arithmetic, children and adults often struggle to acquire its structure and fail to consistently follow the order of precedence when performing operations (Landy & Goldstone, 2010; M.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the facts, experiences, and observations, when teachers encounter problems regarding professional competencies that require conceptual understanding or problem-solving immediately, formal teacher development is felt to be lacking. Conceptual understanding, particularly in mathematics, includes not procedural understanding but also relational understanding that relates to various mathematical concepts (Jupri et al, 2021;Skemp, 1976). Meanwhile, problem-solving, which needs higher-order thinking skills, requires teachers to think critically, creatively, and non-routinely Koichu & Leron, 2015;Polya, 1973;Posamentier & Stepelman, 1990;Samo, 2017).…”
Section: Introductionmentioning
confidence: 99%